Effect of probionts on the growth, food utilization and biochemical changes in pearl spot Etroplus suratensis (Bloch) - Immanuel, G; Menenthira, V; Beena, S; Palanivesam, A (Indian Journal of Fisheries, 2011)
To evaluate the efficiency of different probionts (Lactobacillus and Yeast) onÂ Etroplus suratensis, three different pelleted diets were formulated with 30%Â protein and in which two diets were supplemented with probionts such as 2%Lactobacillus Â (diet A) and 2% yeast (diet B) and a diet (C) without probiont wasÂ used as control. The water stability of these diets was studied as a function ofÂ exposure duration. The leaching percentage during 6 hrs period did not varyÂ much between experimental diets (17.60 to 18.70%). The specific growth rate ofÂ E. suratensis revealed that the control diet fed fish have the lowest value ofÂ 2.93% against the highest values of 3.62 to 3.82% in probionts supplementedÂ diets fed fishes. The gross production efficiency was also higher in probiontssupplemented diet fed groups than control group.